2008
DOI: 10.1016/j.jacc.2008.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter-Defibrillator Therapy for Primary Prevention of Sudden Death After Alcohol Septal Ablation of Hypertrophic Cardiomyopathy

Abstract: The annual rate of appropriate ICD discharges after ASA is low and less than that reported previously for primary prevention of SCD in HCM. This suggests that ASA is not proarrhythmic. Traditional SCD risk factors did not predict ICD shocks in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 42 publications
2
58
0
3
Order By: Relevance
“…In the last decade, a large body of literature (including a number of meta-analyses) has reported the results of this procedure (13,(22)(23)(24)(25)(26). Alcohol septal ablation can often relieve obstruction and improve symptoms (at least during an intermediate period of follow-up) when performed in properly selected patients by interventional cardiovascular specialists with extensive experience with this procedure (13,22,24,25). However, a note of caution should be raised regarding limitations of the literature on alcohol ablation.…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, a large body of literature (including a number of meta-analyses) has reported the results of this procedure (13,(22)(23)(24)(25)(26). Alcohol septal ablation can often relieve obstruction and improve symptoms (at least during an intermediate period of follow-up) when performed in properly selected patients by interventional cardiovascular specialists with extensive experience with this procedure (13,22,24,25). However, a note of caution should be raised regarding limitations of the literature on alcohol ablation.…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%
“…These small arteries form an intricate network of anastomoses that may either limit the area of myocardial ischemia to segments of the septum that do not contribute to outflow obstruction or extend ischemia to other areas of the left ventricle with the potential for widespread myocardial damage (31)(32)(33). This difficulty in predicting the myocardial distribution of alcohol is also the basis for the 10% to 15% rate of complete heart block and permanent pacemaker implantation, as the conduction system is located in the posterior ventricular septum and consequently exposed to damage by the injected ethanol (1,8,12,22,25,30). The risk of such complications is directly related to operator and institutional experience with the alcohol septal ablation procedure.…”
Section: Technical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the incidence for reentrant ventricular tachyarrhythmias and sudden death originating from the alcohol-induced myocardial necrosis and scarring in the patient with HCM, a patient who already has preexisting electrical instability and an unpredictable myocardial substrate [18]. Recent reports suggest that lethal arrhythmogenic events linked to ablation may not be uncommon [19,20]. In addition, alcohol septal ablation has also been associated with increased firing of implantable cardioverter defibrillators [13].…”
Section: Limitations Of Asamentioning
confidence: 99%
“…Such fears were heightened by some small observational studies, 32,33 but these were contradicted by other similar studies that indicated the technique was safe. 34,35 These conflicting results, and the lack of sufficient evidence, have created confusion that can only be resolved by large studies of patients treated by ASA with long-term outcomes and by meta-analyses comparing the results of the two techniques. In 2008 Kuhn et al published the results of 644 consecutive patients treated by ASA over a 10-year period.…”
Section: Comparison With Myectomymentioning
confidence: 99%